KARAKTERISTIK BIO-OIL SERBUK GERGAJI SENGON MENGGUNAKAN PROSES PIROLISIS LAMBAT - Santiyo Wibowo1 (BRIN Publishing, 2013)
Bio-oil is a dark-colored liquid fuels derived from biomass such as wood, bark and other biomass waste from forestryand forest products industry through pyrolysis technology. Bio-oil can be used in industries as a fuel for boilers or direct fuelfor drying purposes such as fuel oil.The purpose of this study is to get information of production technology from sengon ( Paraserianthes falcataria L. Nielsen) sawdust using slow pyrolysis. the sawdust was heated with limited air at temperature 350 -500 C in 30 - 60minutes. The variables used in this study are temperature and duration of pyrolysis. The results showed that optimumbio-oil produced by treatment 500 C for 30 minutes, with the following characteristics; yields of liquid was 43.75% andbio-oil yields 7.95%, phenol 3.80, pH 2.84, specific gravity 1.116 g/cm , heating value 22.42 MJ/kg and flame powerwas medium power. Bio-oil produced by thisprocess predominantly composed of acetic acid and phenols. In addition, thereare several components that include combustible fuel i.e. 2-propanone (CAS) acetone, benzene, 1,2,4 trimethylbenzene,and 2-Furanmethanol (furfuryl alcohol).